Plan de marketing para el tecnicentro Shushufindi del cantón Shushufindi, de la provincia de Sucumbíos, período 2015-2019 - Veloz Olalla, Yessi Silvana (2016)
This research work called "MARKETING PLAN FOR THE CANTON TECNICENTRO SHUSHUFINDI SHUSHIFINDI OF SUCUMBÍOS PROVINCE, PERIOD 2015-2019", it was made in the province of Sucumbíos, Shushufindi, Tecnicentro Shushufindi city of Shushufindi, where it could investigate through primary and secondary sources and perform the field work that allowing drafting the Marketing Plan. To conduct this research, it was necessary to have a theoretical basis, that is to say issues related to the organization, marketing plan, marketing, SWOT analysis, research methodology, which helped structure the Marketing Plan to be addressed the Tecnicentro city Shushufindi. The research has overall objective Develop a Marketing Plan for the Tecnicentro Shushufindi, the Shushufindi, Sucumbíos province; for which purpose it was necessary to have specific objectives which are: Diagnosing the situational status Tecnicentro Shushufindi; define the commercial characteristics of the products, goods or services offered by the Tecnicentro Shushufindi its customers; analyze the environment, the geographical scope, area of influence, competition, suppliers, potential clients, as figures involved in the purchasing process; segment customers and define their buying habits and consumption; define pricing strategy and calculation of margins as determining factors for the increase in sales; propose a sales forecasting system as backup methodology in times of seasonality and drafting a five-year Marketing Plan. The research was performed taking into account the provisions of scientific method, and different research methodologies such as deductive, inductive methods; and techniques such as the survey and direct observation; thus facilitating the development of research work; concluding that research is a valuable contribution to the Tecnicentro Shushufindi and society. In the results, after collecting the information it was necessary tabulation, analysis and interpretation of data obtained in the interview survey, internal and external analysis, information on the SWOT matrix and the matrix of strategies that led to proposing the objectives condensed strategic for Tecnicentro Shushufindi are: Strengthen the degree of reliability of Tecnicentro Shushufindi. Increase participation Tecnicentro Shushufindi in the market and retain current ones. Search for new market niches. Position the mark. Provide added value to the products and services offered by the Tecnicentro Shushufindi. Subsequently the conclusions and recommendations arising from field research were raised. Finally there is the use of literature and Web resources, describing books, texts, which served the same reference source. Models interview, survey, photographic material, etc., were located in the Annex.